Pendidikan Pesantren dalam Bingkai Pendidikan Nasional - Asmuni, Hadiqoh (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
Islamic boarding schools are the oldest Islamic educational institutions in Indonesia and make important contributions in the socio-religious field. Islamic boarding schools as educational institutions are able to maintain and maintain their survival (survival system) and have multi-aspect education. Islamic boarding school education needs to be developed and adapted to what is set by "National Education" so that pesantren education graduates have a competitive and creative advantage in accordance with national and international education quality standards. As part of the community infrastructure, macro-boarding schools make the community aware of having idealism, intellectual abilities, and noble behavior (akhlaqul karimah) to organize and build a complete national characteristic. This can be seen from the strategic message of the pesantren which was developed in the internal culture of the pesantren education. The pesantren education system that has been maintained has turned out to have significant results in building an effective learning atmosphere and learning process. Being an obstacle to national education in rejecting changes in the era of technology and information requires the reconstruction of the national education system by looking at the needs of today's global society. Seeing the multiplicity of pesantren in people's lives, it cannot be denied that Islamic boarding schools have great potential to building a nation that is more moral, personable and knowledgeable. Seeing the condition of national education which unable to overcome social problems, pesantren appear in improving the weaknesses of national education and supporting national goals. Evidenced by the existence of community empowerment institutions that handle various community issues both in terms of economic, political, cultural and educational.